A clinicopathological study of oral premalignant and malignant lesions with a special focus on gingivobuccal complex in a tertiary care center - Rashmi Rekha Mahapatra,; Rupa Das,; Kalyani Prava Gouda,; KCKDN Hembram,; Tribikram Debata,; Manas Ranjan Satpathy, (Asian Journal of Medical Sciences, 2023)
Background: Globally, oral cavity lesions are a serious public health issue. Premalignant lesions of the oral cavity, such as leukoplakia, erythroplakia, and oral submucous fibrosis, are common in India and are strongly associated with tobacco and betel nut use. These lesions have the potential to transform into malignancies, with squamous cell carcinoma (SCC) being the predominant type of oral cancer. Early detection and effective management of early malignant lesions are crucial to improving the prognosis for patients. Histopathological examination is a standard procedure used to identify these lesions. Aims and Objectives: The objective of this study is to examine the histopathology of premalignant and malignant lesions of the oral cavity, taking into account age, sex, site distribution, and their association with tobacco consumption. Materials and Methods: The study was a prospective, observational study carried out over a period of 3 years on patients with lesions of the oral cavity in a Government Medical College of Northern Odisha. Biopsies were obtained, fixed, and routinely processed. Sections were stained with Hematoxylin and Eosin. The final diagnosis was based on clinical, gross, and microscopic findings. The data was collected and analyzed. Results: Out of a total of 197 oral biopsies, 79 cases were malignant lesions, and 35 cases were pre-malignant lesions. The highest incidence of both pre-malignant and malignant lesions was observed in the age group of 51–60 years, with a male predominance. The buccal mucosa was the most affected site. The most frequent type of malignant lesion was well-differentiated SCC, while hyperkeratosis without dysplasia was the most common type of pre-malignant lesion. Conclusion: Cancers of the oral cavity are surface malignancies whose signs and symptoms can be recognized early. The most common subsite of cancer is the gingivobuccal complex, and site-specific carcinoma is often due to the use of tobacco and betel quid, as they are typically placed in the gingivobuccal sulcus. The occurrence of carcinoma can be minimized by creating public awareness regarding high-risk habits.